Preparation and Protective Performance of High-Reflection and High-Thermal Insulation Laser Protection Coatings - LI Shuwen, WU Lingfeng, YANG Guanjun, CHEN Lin (Cailiao Baohu)
Laser weapons have entered the actual combat application stage， and the research on anti-laser protection for air and space weapons is becoming increasingly urgent.Prolonged high-energy laser irradiation leads to problems such as reduced metal reflectance，mass loss of ablated layer of the ablative layer and insufficient heat insulation toughness.Based on this，a composite laser protection strategy based on the principles of reflection and heat insulation was proposed.In this study， by adjusting spraying power， spraying distance and other parameters， supersonic flame spraying technology and plasma spraying technology were used to prepare NiCoCrAlTaY bond coating and yttria-stabilized zirconia(YSZ) top coating double-layer coatings， to explore the influence of surface roughness and porosity on reflectivity， and to investigate the laser protection performance of the coatings.Results showed that the larger the spraying power or spraying distance， the more obvious the layer effect， and the more cross-sectional pores were observed in the coating.The surface roughness of the coating decreased first and then increased with the increase in spraying distance.When the secondary reflection structure was removed， the coating surface had Ra＝1.8 μm.When Ra＝0.5 μm， the wedge-shaped structure of the coating increased the reflectivity by about 2.4%compared to that of the coating when Ra＝1.8 μm.It was pointed out that the layered pores were key to the high-reflection wedge structure， the spherical voids were the laser absorption points，and the process parameter of 14.7%porosity (39 kW，100 mm) was the best.In the laser ablation experiment，with the increase in laser power density， the cracks in the coating gradually increased until holes were ablated.The line ablation rate increased approximately in a parabolic manner.With low laser power density (<3 800 W/cm2)， the surface structure changed slightly； as the power increased， the surface cracks increased and deepened， and the petal-like structure in the recondensing zone increased.With high laser power density (>8 050 W/cm2)， partial peeling and ablation of the coating surface caused the coating to fail.